Nummular eczema in children and adults: clinical picture and differential therapy approaches - D. B. Proshutinskaia; P. A. Skripkina (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article deals with present-day ideas on pathogenesis and treatment of Nummular eczema, differences between clinical I picture of the disease with children and adults.